Validation of Sistem Pelatihan Otak or SiPETA A Digital Cognitive Remediation Therapy for Children - dewi, Suzy Yusna; Pasiak, Taufiq Fredrik; Theresa, Ria Maria; Harfiani, Erna (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
The development of cognitive abilities is closely related to children's academic achievement and behavioral issues. Children prefer media that use visual and auditory elements to optimize their attention. Therefore, media are needed to enhance attention and memory, thus improving their understanding of lessons and impacting academic performance. This study aims to validate SiPETA as a digital cognitive remediation therapy for children to enhance learning abilities. SiPETA was developed based on a prototype of learning methods focused on Attention, Memory, and Self-Regulation. The platform contains social intelligence stories based on Bloom's taxonomy, categorizing cognitive abilities into six levels. The research method includes three stages. In the first stage, face validity was tested by 13 experts in child development and special education who evaluated the platform's narratives using the Delphi method. In the second stage, content and construct validity of SiPETA were tested by experts using the Lawshe method. In the third stage, the usability of the SiPETA application was tested on 12 elementary school children using the Lawshe method. The results showed that SiPETA is valid, reliable, and ready for training. SiPETA can be a valuable tool for teachers and parents to help children develop cognitive skills and improve academic achievement.